Pemodelan Aplikasi Pengadaan Barang Menggunakan Metode Waterfall - Arizka Anggraini; Latifa Khoirani; Armansyah Armansyah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Procurement of goods is a recurring activity in a company's business process. Meanwhile, the traditional goods procurement process is often felt to be less efficient and effective, so it requires a better solution. The traditional procurement process also often takes a long time, has high costs and lacks transparency. This can lead to inefficiencies and risks of abuse. This research aims to develop a more efficient and effective goods procurement application model using SDLC and waterfall methodology. This research uses observation methods to study the current procurement process and interviews to obtain input from stakeholders regarding application needs. The research results show that the goods procurement application model developed can help companies in the goods procurement process more efficiently and effectively. This application model can help companies save time and costs, as well as increase transparency and accountability in the procurement process.